Fungsi Pengawasan Dewan Perwakilan Rakyat Daerah terhadap Pelaksanaan Anggaran Stunting Tahun 2021-2022 di Kabupaten Timor Tengah Selatan - Tikwa Petronela Selan; Saryono Yohanes; Yosef Mario Monteiro (LPPM Universitas Sains dan Teknologi Komputer, 2024)
The purpose of this study is to analyze the supervisory function of the regional people's representative council on the implementation of the 2021-2022 stunting budget in South Central Timor District. The type of research used by researchers is empirical legal research. The types of data used in this research are primary data, secondary data, and tertiary data. Data collection techniques using interviews, observation, and literature/documentation studies. The population in this study includes all parties involved in the function of the South Timor Tenggah Regency Regional House of Representatives in supervising the stunting budget in South Timor Tenggah Regency, namely, the Health Office, DPRD members, and the community. The sample technique used in this study was purposive sampling. Data processing techniques through editing, coding, tabulation, and verification. The result of this study is that the Government of Indonesia is very serious in dealing with the problem of stunting in Indonesia so that the government issued several regulations in order to prevent and control stunting in Indonesia. The regulation of the supervisory function by the DPRD on the implementation of the stunting budget has not been implemented properly due to the lack of communication between the executive and the legislature.